Defining the visual adaptation field for mesopic photometry: Effect of surrounding source position on peripheral adaptation. (October 2017) - Uchida, T; Ohno, Y
In CIE 191:2010, the Commission Internationale de l'Eclairage recommends a mesopic photometry system based on peripheral visual tasks. For implementation of the system, the visual adaptation field needs to be defined, taking into account the surrounding luminance effect on the state of adaptation. A series of vision experiments in the mesopic range has been conducted to measure the surrounding luminance effect with respect to the angle between a peripheral task point and a point source. The results show that the surrounding luminance effect at a peripheral task point decreases with increasing angle at a larger slope than existing models, such as the Stiles-Holladay equation, the Commission Internationale de l'Eclairage general disability glare formula and the Stiles–Crawford equation. A new model for the surrounding luminance effect is proposed.